Analisis Finansial Distress Dengan Menggunakan Metode Zmijewski , Springate Dan Grover - Nyai Ida Ayu Diah; Renea Shinta Aminda; Titing Suharti (CV. ITTC INDONESIA, 2024)
This research aims to determine the level of company bankrupty by using analysis of the Zmijewski Model, Springate Model dan Grover Model for automotive companies listed on the Indonesia Stock Exchange (BEI). Automotive companies have a fairly large role in the Indonesian economy. This research uses these three methods too see how much bankruptcy is predicted in the 2020-2022 period in automotive companies. Calculate each bankruptcy prediction for each company. The data used in this research is secondary data, where data is obtained from available sources. Secondary data in this research uses annual financial reports obtained on the Indonesia Stock Exchange website and the company’s official website. The type of data used in research is quantitative data, where data contains numbers which are carried out objectively by collecting, processing, analyzing and presenting data. The result of the this research indicate that the Score-model can be implemented in detecting the possibility of bankruptcy in automotive companies listed on the Indonesia Stock Exchange. The Zmijewski model and Grover model have the same result in predicting the bankruptcy of a company.